KONTRIBUSI KESEGARAN JASMANI TERHADAP HASIL BELAAJR SISWA SMPS AMPEAN ROTAN KECAMATAN SIMPANG KANAN - Marlina, Lenni; Juita, Ardiah; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the students' SMPS Ampean Rotan Simpang Kanan learning outcomes result was not good enough that found by researcher at the time of observation in the field. Researcher suspect this is because one of the factors, namely physical fitness. This research is a correlational that aims to examine the relationship between variables, namely: the independent variable is the physical fitness (X1) and the dependent variable is the learning outcomes (Y) student at SMPS Ampean Rotan Simpang Kanan. While this research aims to prove whether there is a physical fitness contributes to student learning outcomes SMPS Ampean Rotan. This research data obtained from the 2.4 km run test and MID semester result. The sample in this study is students of class VII Ampean SMPS which amounted to 32 people using total sampling technique. For male students, there is a significant relationship between physical fitness (X1) to learning outcomes (Y) male students SMPS Ampean Rotan Simpang Kanan, obtained rhitung = 0,816> rtabel = 0.576. Physical fitness contributes to learning outcomes male students at SMPS Ampean Rotan Simpang Kanan at 66.59%. Then female studnets, there is a significant relationship between physical fitness (X1) on learning outcomes (Y) female student SMPS Ampean Rotan Simpang Kanan, obtained rhitung = 0.681> rtabel = 0.444. Physical fitness contributes to student learning outcomes SMPS Ampean Rotan Simpang Kanan at 46.38%.Keywords : Contribution, Physical Fitness, Learning Outcomes